Tareas en el proceso de aprendizaje de los estudiantes de noveno año de educación básica del Colegio Técnico Ponce Enríque provincia del Azuay 2012-2013. - Malla Vera, Mayra Liliana (2014)
This research indicates that academic tasks are allows inculcate habits and attitudes related to the cross-cutting objectives such as the ability to work on their own, form a sense of responsibility for learning, self-discipline and time management, develop initiative, a taste for independence and generate studies to solve the problems.